Generative AI for Individuals’ Financial Well-being and Debt Rehabilitation - Toivonen, Nina; Salo-Lahti, Marika; Ranta, Mikko; Haapio, Helena (Springer, 2025)
Technology plays a significant role in today’s over-indebtedness. However, its potential to help people overcome debt problems and maintain good financial health remains largely untapped. The need for alternative, personalized solutions to over-indebtedness is becoming increasingly pressing worldwide, especially since many people struggling with debt do not have access to judicial debt rehabilitation programs. This chapter explores how generative AI (GenAI) could support individuals in financial distress. Using the behavioral COM-B model as a framework for designing effective interventions, we discuss how AI could help improve individuals’ capabilities, opportunities, and motivation to achieve financial well-being, and what solutions already exist for these purposes. Inspired by fitness applications that offer personalized advice, we used OpenAI’s GPT Builder to create “Finance Friend,” a simple prototype of a financial adviser, and explored its potential as a personalized financial coach. While the tool shows great promise for the future of financial coaching, we also emphasize the need for trustworthy technology and regulatory frameworks that promote responsible design, implementation, and use of AI in the context of debt rehabilitation.
Keywords: Access to justice; Artificial intelligence; COM-B model; Debt rehabilitation; Financial health; Fintech; fi=Talousoikeus|en=Business Law|; fi=Laskentatoimi|en=Accounting|; fi=Talousoikeus|en=Business Law|